Functional heterogeneity of Thy-1 membrane microdomains in rat basophilic leukemia cells - Surviladze, Z; Dráberová, L; Kubínová, L; Dráber, P (European journal of immunology, 1998)
Antibody-mediated cross-linking of Thy-1 glycoprotein on the surface of rat mast cells and rat basophilic leukemia (RBL) cells initiates biochemical events which culminate in secretion of allergy mediators. Thy-1, like some other glycosylphosphatidylinositol (GPI)-anchored proteins, forms detergent-insoluble complexes containing protein tyrosine kinases (PTK) and some other molecules which are implicated in the signaling pathway. On the surface of a rat mast cell there are more than 10(6) Thy-1 molecules; however, it is not known which fraction of them is involved in transmembrane signaling, and what exactly is the heterogeneity of Thy-1 complexes. Using sucrose density gradient ultracentrifugation of detergent-lysed RBL cells we found that the density of Thy-1 complexes depended on the detergent used and the lysis conditions employed. Sepharose 4B gel chromatography fractionation followed by density gradient ultracentrifugation revealed both size and density heterogeneity of Thy-1 and Lyn PTK complexes. Cross-linking of surface Thy-1 caused significant changes in the density of these complexes, and an increase in Lyn kinase activity in low/medium-density fractions. Thy-1 in low-density fractions was relatively resistant to cleavage with phosphatidylinositol-specific phospholipase C (PI-PLC). Interestingly, removal of only a small fraction of surface Thy-1 by PI-PLC abolished the cell activation as determined by tyrosine phosphorylation of certain proteins. When Triton X-100 lysates were fractionated at 12000 x g, about 50 % of Thy-1 remained associated with the nuclear/cytoskeleton pellet; this fraction of Thy-1 exhibited an increased sensitivity to PI-PLC. Confocal laser scanning microscopy on fixed cells revealed that the total Thy-1 was relatively homogeneously distributed over the plasma membrane, whereas the PI-PLC-resistant Thy-1 was found mostly in small clusters. The combined data suggest that specialized membrane microdomains enriched in Thy-1 with increased sensitivity to PI-PLC are directly involved in coupling Thy-1 aggregation to transmembrane signaling.
Keywords: Enzyme Activation; vazebná místa; konfokální mikroskopie; Thy-1 Antigens; fosfolipasy typu C; src-Family Kinases; lyasa fosfatidylinositoldiacylglycerolu; skupina kinas odvozených od src-genu; Microscopy, Confocal; krysa rodu Rattus; Binding Sites; Animals; fosfolipasa C fosfoinositidové signalizace; Phosphoinositide Phospholipase C; zvířata; Phosphatidylinositol Diacylglycerol-Lyase; Rats; nádorové buňky kultivované; myši; aktivace enzymů; antigeny Thy-1; Type C Phospholipases; Tumor Cells, Cultured; Mice